The effect of hands-on activity and problem-based learning on achievement of biology students in Enugu state - Nwankwo, Amaka Loretta; Ugwu, Theresa Ukamaka; Ukala, Geoffrey; Benson, Ozichi Okwukwe (Univeritas Papua, 2024)
The research researched the impact of problem-based learning and hands-on activity on the students' academic performance in biology. The study implemented a quasi-experimental design, specifically a non-equivalent control group design with a pre-and post-test design. The study's population consisted of 2691 students from 32 public secondary schools in the Nsukka. We used a multi-stage sampling procedure to sample 85 SS II students from two intact classes. The researchers developed the